2014
DOI: 10.1016/j.jclepro.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Lean and green product development: two sides of the same coin?

Abstract: This paper compares and contrasts the lean product development (LPD) and green product development (GPD) concepts through a systematic literature review including 102 journal publications. The review resulted in 14 findings that were organised according to four dimensions: general, process, people and tools/techniques. A number of similarities between the concepts were found. For example, implementation of both concepts calls for a systems perspective where the dimensions of process-people-tools/techniques are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 113 publications
0
86
0
1
Order By: Relevance
“…Cabral et al, 2012;Mollenkopf et al, 2010;Dües et al, 2013;Hajmohammad et al, 2013a;Hajmohammad et al, 2013b;Kainuma and Tawara, 2006, among others), in production, manufacturing and industrial systems (e.g. Aguado et al, 2013;Azevedo et al, 2012;Besseris and Kremmydas, 2014;Diaz-Elsayed et al, 2013;Moreira et al, 2010;Pampanelli et al, 2014, among others) as well as in the development of new products (Cluzel et al, 2010;Johansson and Sundin, 2014). However, the results of this literature review also indicate that only the works of Esmemr et al (2010) and Verrier et al (2014) have considered both the lean and green paradigms within the transport and logistics sector.…”
Section: Literature Reviewmentioning
confidence: 87%
“…Cabral et al, 2012;Mollenkopf et al, 2010;Dües et al, 2013;Hajmohammad et al, 2013a;Hajmohammad et al, 2013b;Kainuma and Tawara, 2006, among others), in production, manufacturing and industrial systems (e.g. Aguado et al, 2013;Azevedo et al, 2012;Besseris and Kremmydas, 2014;Diaz-Elsayed et al, 2013;Moreira et al, 2010;Pampanelli et al, 2014, among others) as well as in the development of new products (Cluzel et al, 2010;Johansson and Sundin, 2014). However, the results of this literature review also indicate that only the works of Esmemr et al (2010) and Verrier et al (2014) have considered both the lean and green paradigms within the transport and logistics sector.…”
Section: Literature Reviewmentioning
confidence: 87%
“…and based on these explanatory feature the reviewed studies are categorized as below: Keitany and Riwo (2014) explored the inventory management through lean tools, and employed the descriptive research design tool for improving the management approach & participation of all employees; Baines et al (2006) studied the application of environmentally & socially sensitive practices to reduce the negative impact of manufacturing activities and harmonizing the pursuit of economic benefits; Taubitz (2010) stated that safety & health are the fundamental to sustainable growth but green-lean can result in improved organizational performance & customer experience; Marvel and Standridge (2009) presented an improved lean process using simulation modelling and experimentation prior to execution; Arlbjørn and Freytag (2013) examined lean in academic literature of 105 international peer-reviewed journals and concluded that only 1/3 of them apply a toolbox view on lean; Castro et al (2012) reviewed the agile and lean manufacturing concepts along with the information & commutation technological solutions, to resolve the issues in manufacturing sector; Dakov and Novkov (2007) concluded that lean principles leads enterprises towards a more sustainable processes & product development; Romvall et al (2010) indicated that lean & green are the favorable options for environmental sustainability within production system in Sweden; and Nordhaus (1995) analyzed the role of climate in economic development, its relationship and the prospects for economic impacts. Improving the environmental performance also leads to reducing costs, increase competitiveness and to be more innovative across the value chain; Maia et al (2013) discussed lean production in textile industry that fosters a sustainable work environment; Chen and Meng (2010) reviewed the course from mass to lean production and issues in Chinese enterprises; Kurdve et al (2014) focussed on integration of environmental and operations management in two global Swedish companies; Moreira et al (2010) presented the role of lean for achieving better environmental performance and an emergent business model for supporting eco-efficiency by literature review; Johansson and Sundin (2014) compared lean product development (LPD) and green product development (GPD) concepts through a systematic literature review including 102 journal publications; Holweg (2007) presented the research that led to the formulation and dissemination of the most influential manufacturing paradigms of recent times; while, Ogunbiyi et al (2013) strained on lean and sustainability reflecting how it impacts on sustainable construction through literature. …”
Section: Grouping 1: Descriptive Featuresmentioning
confidence: 99%
“…Johansson and Sundin (2014), however, affirm not to be possible to say that actions toward one directly lead to consequences on the other, being this area yet incipient (Garza-Reyes, 2015). Also, potential relations might have been neglected, being this investigation inconclusive (Jabbour et al, 2013).…”
Section: Controversial Literaturementioning
confidence: 86%
“…Even though Lean and Green Manufacturing hold certain harmony, they differ in a few aspects, such as: main focus, process structure, construct value, performance measurements, type of consumers, definition of waste e techniques utilized (Johansson and Sundin, 2014). Under this light, Kleindorfer et al (2005) state that Lean and Green Manufacturing practises are distinct and, therefore, they have different impacts on organisational performance.…”
Section: Controversial Literaturementioning
confidence: 99%
See 1 more Smart Citation